Identifying the determinants of mortgage default in Colombia between 1997 and 2004 (2013)
This paper examines the relationship between mortgage default decisions and relevant observable variables in Colombia between 1997 and 2004. We estimate a discrete choice model of default using a panel of individual mortgage characteristics and payment information. We show that home prices and debt balances are the main determinants of mortgage default. We account for the presence of unobserved heterogeneity using Survey data and simulation techniques. Including controls for the distribution of income shows that income was not important but helps clarifying the relevance of mortgage leverage in the determination of the observed default rates.